Studi Kepustakaan Kemampuan Berpikir Kritis Dengan Penerapan Model PBL Pada Pendekatan Teori Konstruktivisme - Indah Tri Kusumawati; Joko Soebagyo; Ishaq Nuriadin (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2022)
The purpose of this research is to describe critical thinking skills in mathematics learning by applying the Problem Based Learning (PBL) model to the constructivism theory approach. The method used is qualitative through literature study. The research was conducted through the stage of collecting data from library sources. From the results of the study, it can be concluded that students' critical thinking skills can be increased through the application of Problem Based Learning (PBL) learning models in constructivism theory approaches. Constructivism theory and Problem Based Learning (PBL) learning models are considered effective and efficient in developing children's cognitive. This learning model raises curiosity and increases motivation so that it can develop higher thinking skills, especially in critical thinking.